(untitled) (Contemporary Mathematics, 2024)
Geostatistics is a subdomain of statistics that deals with phenomena which have spatial or spatiotemporal distribution. This paper proposes an extension of properties of the multivariate F-alpha variogram within a spatial framework and in a max-stable random field with unit Fréchet margins. We use the copula associated with the distribution of the fields to model the multivariate F-alpha variogram while important properties of this dependence measure are discussed for spatial extreme events. The hypothesis of normality and the consistency of two non-natural estimators are investigated.